Adventure Game Development for Environmental Conservation Using Game Development Life Cycle - Nisa Rizqiya Fadhliana; Naufal Andrian; Diva Rajestiadi; M. Bintang Kurninawan (Computer Science (CO-SCIENCE), 2026)
The rapid development of information and communication technology has driven innovation in various fields, including digital entertainment through video games. This research develops an educational adventure game themed on environmental conservation titled Green Solaris, designed as an interactive medium to raise awareness about environmental issues among children and teenagers. The game adopts a 3D isometric format with a pixelated visual style, focusing on four main themes: Clean Water and Sanitation, Affordable and Clean Energy, Climate Action, and Life on Land. The development process employs the Game Development Life Cycle (GDLC) methodology combined with Agile-SCRUM approach, encompassing six main phases: initiation, pre-production, production, testing, beta, and release. The game features core mechanics including exploration, interaction with NPCs, waste collection and recycling systems, point-based upgrades, and environmental restoration missions across multiple islands. Testing results using Likert scale instruments show that 90% of respondents rated the game as "Very Satisfying" and 10% as "Quite Satisfying" with no negative assessments, indicating the game's potential as an effective educational medium. Green Solaris has been successfully published on the itch.io platform and is accessible to the public, demonstrating that video games can serve as an innovative and engaging alternative learning tool for instilling environmental awareness through creative, interactive, and educational digital experiences.